Assessment of nutrient and heavy metal contamination in surface water and sediments of the upper Tigris River, Turkey - Varol, Memet; Sen, Bulent (Elsevier, 2012)
The concentrations of total nitrogen (TN), total phosphorus (TP), As, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn in both surface water and sediment samples from the upper Tigris River were determined to evaluate the level of contamination. All metal concentrations in water samples, except Cu, were lower than the maximum permitted concentration for the protection of aquatic life. TN. TP and metal concentrations in sediment samples from the first three sites situated downstream of Ergani Copper Mine Plant were much higher than those at other sites. There was a significant decrease in the concentrations of heavy metals in sediment from the last site downstream of the Dicle Dam. Sediment pollution assessment was undertaken using enrichment factor (EF) and geoaccumulation index (I-geo). The sediments of sites downstream of the copper mine plant showed significant enrichment with Cd, Co, Cu, Pb and Zn, indicating metallic discharges from the Ergani Copper Mine Plant. The I-geo values revealed that Cu (5.09), Co (426) and Zn (3.18) were significantly accumulated in the study area. Based on the comparison with sediment quality guidelines, the concentrations of Cr. Cu, Ni, Pb and Zn at sites downstream of the copper mine plant are likely to result in harmful effects on sediment-dwelling organisms. Cluster analysis suggests that As, Cd, Co, Cu, Ni, Pb and Zn are derived from anthropogenic sources, particularly metallic discharges of the copper mine plant. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Metals; Enrichment factor; Geoaccumulation index; Water and sediment quality guidelines; Cluster analysis; River pollution